Repeat Revascularization for Severe Recurrent Coronary Artery Disease in a Young Woman With Takayasu Arteritis - Madhavan, Mahesh V. (JACC Case Rep, 2020)
A young woman with Takayasu arteritis presented with an acute coronary syndrome with ostial left main coronary artery stenosis. She underwent urgent coronary artery bypass surgery but developed recurrent symptoms 6 months later owing to graft failure. She was treated with percutaneous coronary intervention with resolution of her symptoms. (Level of Difficulty: Beginner.)